1999
DOI: 10.1117/12.353034
|View full text |Cite
|
Sign up to set email alerts
|

<title>Invariant subpixel target identification in hyperspectral imagery</title>

Abstract: We present an algorithm for subpixel material identification that is invariant to the illumination and atmospheric conditions. The target material spectral reflectance is the only prior information required by the algorithm. A target material subspace model is constructed from the reflectance using a physical model and a background subspace model is estimated directly from the image. These two subspace models are used to compute maximum likelihood estimates for the target material component and the background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…In this section, we consider the class of f(x) = (2r)'2IFI112h(d) (1) where d is a quadratic form (Mahalanobis distance) defined by d=(x_t)TF_l(xji) (2) and h(d) is a positive, monotonically decreasing function for all p. We shall denote such a distribution using the shorthand notation EC(t, F, h).…”
Section: Random Vectors With Elliptically Contoured (Ec) Distributionsmentioning
confidence: 99%
“…In this section, we consider the class of f(x) = (2r)'2IFI112h(d) (1) where d is a quadratic form (Mahalanobis distance) defined by d=(x_t)TF_l(xji) (2) and h(d) is a positive, monotonically decreasing function for all p. We shall denote such a distribution using the shorthand notation EC(t, F, h).…”
Section: Random Vectors With Elliptically Contoured (Ec) Distributionsmentioning
confidence: 99%
“…The rarity of the target is a very important requirement in this respect; however, it is helpful to remove target-like pixels (that is pixels with large projections |Sjx(n) || onto the target subspace) before computing the eigendecomposition or the SVD. Target leakage can be also reduced by excluding eigenvectors or singular vectors with large projections ||Sfil*|| onto the target subspace [61]. Figure 18 illustrates that a three dimensional subspace can be used to accurately model the spectral variability of the selected target.…”
Section: Subspace or Low-rank Data Modellingmentioning
confidence: 99%
“…Background characterization for the detection of low-probability targets can be done using the eigenvectors [11,56] of the HSI cube correlation matrix R x = X 1 X/N or equivalently the singular vectors [61] of the data matrix X T . In the first case, matrix S b is formed by the first Q significant eigenvectors of R x .…”
Section: Subspace or Low-rank Data Modellingmentioning
confidence: 99%
“…It has been shown that use of hyperspectral information is useful for detection of objects in military applications such as detecting military vehicles [1,2,23] and mines [3,23], for land use applications [4], and for many USDA product inspection applications [5][6][7][8][9][10][11][12]. This occurs since HS data provides spectral information that uniquely characterizes and identifies the chemical, moisture, and physical properties of the constituent parts of an input object, scene region, or an agricultural product.…”
Section: Introductionmentioning
confidence: 99%